The Concept of ‘Aql in the Formulation of Matn Hadith Criticism: A Conceptual Study of Muhammad al-Ghazali’s Thought in His Work as-Sunnah an-Nabawiyyah baina Ahl al-Fiqh wa Ahl al-Ḥadīṡ - Aulassyahied, Qaem; Yunainti, Fitria Sari; Kholis, Nur (Universitas Ahmad Dahlan, 2024)
This study aims to investigate the role of ‘aql in the criticism of the matn of hadith by Islamic scholars. In religious studies, hadith is one of the primary sources for understanding Islam and the practice of Muslim life. However, with the progression of time, a need has emerged to reassess this method from a contemporary scientific perspective. This is evident in the application of scholars in assessing hadith using the indicator of ‘aql, which varies among them. More specifically, the background of this research is based on several facts. First, hadith scholars have paid more attention to the development of sanad criticism than the matn. This points to the statements of contemporary scholars that the discussion and research on hadith have focused more on analyzing and developing the theory of sanad. Second, scholars who recognize ‘aql as a criterion for matn criticism exhibit varying applications of this concept, with these differences already evident since the time of the Prophet's companions. The research methodology will involve literature studies, hadith text analysis, and exploration of the thoughts of Islamic scholars and intellectuals regarding the use of ‘aql in matn criticism.